Effects of Destruxin A on Hemocytes Morphology of Bombyx mori - Ji-qiao FAN; Xiu-run CHEN; Qiong-bo HU (Journal of Integrative Agriculture, 2013)
Destruxin A (DA), a kind of cyclo-hexadepsipeptide isolated from entomopathogenic fungus, Metarhizium anisopliae, is an inhibitor of insect's immunity. But its mechanism has not been clarified yet. In this study, the effects of DA on morphologic changes of in vivo and in vitro hemocytes of silkworm, Bombyx mori, were investigated by means of inverted phase contrast microscopy (IPCM), fluorescence microscopy (FCM) and environmental scanning electron microscopy (ESEM). The results indicated that DA was cytotoxic to granulohemocytes (GR) and plasmatocytes (PL). The LC50 values of DA against in vitro GR and PL of silkworm were 68.77 and 84.11 µg mL−1, respectively. However, the hemocytes in vivo were more susceptible to DA, although at the extremely low dose of 10 µL of 12.5 µg mL−1 for each insect (i.e., 0.036 µg g-1 body weight, or approximately 0.25 µg mL−1 hemolymph), DA could induce obviously morphologic alterations of hemocytes in vivo. The results imply that there might be some factors in silkworm's hemolymph, which influence the interaction of DA and hemocytes.